Predictors of Outcome Difference Following Acute Myocardial Infarction between Rural and Urban Patients - Rahim, Mohammed Abdur; Bashiruddin, A B K; Mahmud, Iqbal; Bhattacharya, Debabrata; Awal, Anisul; Das, Prabir Kumar; Islam, Neena; Rouf, Md Abdur; Alam, Muhammed Syedul (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: Different factors may influence management, complications and outcome of both rural and urban patients following Acute Myocardial Infarction (AMI). Aim of the study was to identify the factors influencing outcome following AMI between rural and urban population is lacking in our country. Materials and methods: This was a cross sectional study carried out in the Department of Cardiology, CMCH from June 2018 to May 2019. One hundred and ninety-eight consecutively admitted AMI (STEMI) patients from both urban and rural area were included. Demographic, anthropometric, risk factors, presentation profile, inhospital complications and outcome were recorded and compared between the groups. Results: Out of 198 patients 23.23% female and 76.23% were male. Mean age was significantly higher in Rural group (55.5±11.6 years) than the Urban (49.3±11.2 years) p value 0.037. Urban patients were more sedentary (68.8% vs. 43.8%, p=0.001) and having higher BMI (>25kg/m2 was 48.8% vs 30.6%, p=0.024). Rural patients presented late after symptom onset (5 hours vs. 13 hours) long distance to travel was mentioned as prime cause of delay by them. Inhospital mortality was higher among rural patients (12.4% and 3.9%; p=0.045). Adverse outcome was associated with increasing age, male sex and poor LV function in urban patients, while in rural patient it was related to lower education level, delayed presentation and poor LV function. Conclusion: Outcome of AMI differs between rural and urban patients. This finding of different factors influencing outcome in two groups could be used to design specific preventative measures. JCMCTA 2021 ; 32 (2) : 20-24